UNCOVERING USA PRESIDENTIAL DEBATE GENRE - Surtikanti, Monika Widyastuti; Purnomo, Kristian Anggi (Universitas Islam Sumatera Utara (UISU), 2023)
Presidential debate (PD) draws the most attention compared to other political discourses as the candidates present their profile and proposals using rhetorical communicative strategy to convince voter candidates and defeat their adversaries. However, the generic structure of PD is seldomly being the perspective of linguistics studies. The paper aims at scrutinizing the genre of USA Presidential debate using the genre analysis framework proposed by Swales and Bhatia. Thus, the study employs two parts of genre analysis: move, and strategies analysis. The present study finds that there are six moves of USA PD namely greetings-informing the debate format, introducing the topic, thesis, argumentation, and closure. The communicative purpose of the moves is persuading the American voters in the election day. The finding implies pivotal stages of PD to construct political discourse. This study is expected to contribute to EFL teaching and learning especially in teaching genre exposition integrated in four English skills.